Social knowledge and modernity The emergency of an epismetic speech in Latin America - Mejía Navarrete, Julio Víctor (2017)
From ends the fifteenth century European globalization of knowledge involves the supremacy of reason that comes together in a unit with modernity domination and colonialism. However, in Latin America they have always been developed epistemic response times of the process of globalization of knowledge modern and colonial. The origins of alternative thinking are at the very roots of the colonization of America. In Latin America and a time of discussion and criticism is opened, a plurality of perspectives that involve the development of proposals to distance themselves from Eurocentric discourse tested.